2022
DOI: 10.51694/advweedsci/2022;40:00020
|View full text |Cite
|
Sign up to set email alerts
|

Use of a wiper applicator for the control of the invasive species Eragrostis plana with glyphosate salts

Abstract: Background: Eragrostis plana is an invasive plant in native grassland areas associated with degradation of the Pampa biome. Selective control of E. plana is difficult due to its similarity to other grassland species. There is a lack of information about E. plana control using selective herbicide application equipment. Objective: The present study aimed to evaluate the efficacy of a pressurize rope wick applicator for controlling the invasive plant E. plana as function of different salts of glyphosate, applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Technical support from the Brazilian Agricultural Research Corporation (Embrapa) teaches farmers how to use the machine properly, without damaging the grassland (Pérez, 2010;Perez, 2015;Faleiro et al, 2022;Merotto et al, 2022).…”
Section: Chemical Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Technical support from the Brazilian Agricultural Research Corporation (Embrapa) teaches farmers how to use the machine properly, without damaging the grassland (Pérez, 2010;Perez, 2015;Faleiro et al, 2022;Merotto et al, 2022).…”
Section: Chemical Controlmentioning
confidence: 99%
“…Bastiani et al (2021) found that the potassium salt in glyphosate had the fastest activity in different E. plana growth stages, but panicle initiation was the most vulnerable, and adding ammonium sulphate to the herbicide mix tank increased the control of drought‐stressed plants. According to Merotto et al (2022), glyphosate diammonium salt, applied with a wiper applicator (8–40 L ha −1 volume application), was the most effective formulation when applied in summer at 1440 g ae ha −1 .…”
Section: Invasion Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…While these ecosystems host endemic species that traverse watercourses, they are also susceptible to invasions due to substantial pressure of propagules [2]. Invasive exotic species can cause changes in the native community, such as the extinction of macrophytes, amphibians, and fish [1,3]; it is estimated that global expenditures on combating biological invasions have reached approximately USD 1.3 trillion since 1970 [4].…”
Section: Introductionmentioning
confidence: 99%